HUBUNGAN PROCALSITONIN DAN GAMBARAN MORFOLOGI LEUKOSIT PADA INFEKSI BAKTERIAL - Fenty Fenty; Dita Maria Virginia (Universitas Sanata Dharma, 2016)
Abstract: Bacterial sepsis increases morbidity and mortality in all ages. Early detection has been shown to be crucial for the improved outcome of patients with sepsis. Till now there is no routine test for screening. Procalcitonin and morphology of leukocytes are biomarkers of bacterial sepsis. The aim of this study was to determine the relationship between procalcitonin and morphology of leukocytes as marker in bacterial infection. This study was analytical observational with cross sectional design and data collected prospectively.This study measured simultaneously the value of procalcitonin and morphology of leukocytes examination in patients with suspected bacterial infection in hospital X of Yogyakarta. Data were analysed by statistics. The results showed immature granulocytes and vacuolization of neutrophils in the leucocytes morphology has a significant correlation with level of procalcitonin. Keywords: bacterial infection, procalcitonin, morphology of leukocytes